Non-invasive Brain Stimulation, a Tool to Revert Maladaptive Plasticity in Neuropathic Pain - Naro, Antonino; Milardi, Demetrio; Russo, Margherita; Terranova, Carmen; Rizzo, Vincenzo; Cacciola, Alberto; Marino, Silvia; Calabro, Rocco S.; Quartarone, Angelo (Frontiers in Human Neuroscience, 2016)
Neuromodulatory effects of non-invasive brain stimulation (NIBS) have been extensively studied in chronic pain. A hypothetic mechanism of action would be to prevent or revert the ongoing maladaptive plasticity within the pain matrix. In this review, the authors discuss the mechanisms underlying the development of maladaptive plasticity in patients with chronic pain and the putative mechanisms of NIBS in modulating synaptic plasticity in neuropathic pain conditions.